2018
DOI: 10.1093/cercor/bhy144
|View full text |Cite|
|
Sign up to set email alerts
|

An Autonomic Network: Synchrony Between Slow Rhythms of Pulse and Brain Resting State Is Associated with Personality and Emotions

Abstract: The sympathetic system’s role in modulating vasculature and its influence on emotions and personality led us to test the hypothesis that interactions between brain resting-state networks (RSNs) and pulse amplitude (indexing sympathetic activity) would be associated with emotions and personality. In 203 participants, we characterized RSN spatiotemporal characteristics, and phase–amplitude associations of RSN fluctuations with pulse and respiratory recordings. We found that RSNs are spatially reproducible within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 130 publications
(154 reference statements)
1
22
1
Order By: Relevance
“…Large amplitude peaks or transients in the BOLD, however, in addition to neural events may also reflect motion (Power et al, 2012) and physiological noise, such as spontaneous fluctuations in arterial CO2 (Golestani et al, 2016;Prokopiou et al, , 2016, cardiac pulsatility (Glover et al, 2000), respiration and heart rate variability (Birn et al, 2008;Chang et al, , 2009Kassinopoulos and Mitsis, 2019). These non-neuronal sources of BOLD signal variability have been shown to elicit networks of coherent BOLD activity, which resemble previously reported resting-state networks derived from fMRI data (Chen et al, 2019;Nalci et al, 2019;Nikolaou et al, 2016;Shokri-Kojori et al, 2018). In addition, covariation of the BOLD signal in different brain regions that is sufficient to give rise to spatial patterns of resting-state activity can be also observed at the timings of lower amplitude peaks, or even at regularly or randomly selected timepoints along the time course of the signal.…”
Section: Introductionsupporting
confidence: 74%
“…Large amplitude peaks or transients in the BOLD, however, in addition to neural events may also reflect motion (Power et al, 2012) and physiological noise, such as spontaneous fluctuations in arterial CO2 (Golestani et al, 2016;Prokopiou et al, , 2016, cardiac pulsatility (Glover et al, 2000), respiration and heart rate variability (Birn et al, 2008;Chang et al, , 2009Kassinopoulos and Mitsis, 2019). These non-neuronal sources of BOLD signal variability have been shown to elicit networks of coherent BOLD activity, which resemble previously reported resting-state networks derived from fMRI data (Chen et al, 2019;Nalci et al, 2019;Nikolaou et al, 2016;Shokri-Kojori et al, 2018). In addition, covariation of the BOLD signal in different brain regions that is sufficient to give rise to spatial patterns of resting-state activity can be also observed at the timings of lower amplitude peaks, or even at regularly or randomly selected timepoints along the time course of the signal.…”
Section: Introductionsupporting
confidence: 74%
“…Nevertheless, the relevance of these morphological findings remains to be determined. Our work is limited to assessing activity demand and metabolic supply from a static perspective, but future work should involve studying dynamic changes in rPWR and rCST due to physiological 51 or circadian 52 interactions with brain function, using concurrent imaging of neuronal activity (e.g., measures of glutamatergic function or lFCD) and cerebral metabolic supply (e.g., CMRglc or CBF 53,54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Module 1 contained left inferior temporal regions including the parahippocampal gyrus and posteromedial regions. Interestingly, an autonomic network identified in a previous fMRI study was composed of regions showing stronger interactions with low-frequency peripheral pulse amplitude fluctuations (occurring at ∼0.01–0.09 Hz) than with other brain regions (Shokri-Kojori et al, 2018), and the network had some topological overlap with module 1 such that it also contained a large portion of posteromedial regions and the parahippocampal gyrus. Notably, this previous study also used an HCP dataset (fMRI and behavior data, 18 participants in the previous study were also included in our study) as in our study.…”
Section: Discussionmentioning
confidence: 96%
“…In the recent reviews of Azzalini et al (2019), authors mentioned that because HRV was reported to be largely driven by the brain, the HRV-associated resting-state brain networks are likely to be associated with descending influences from the brain to heart (Azzalini et al, 2019). Another recent fMRI study showed regions associated with a low-frequency peripheral pulse fluctuation called an autonomic network (Shokri-Kojori et al, 2018). Based on these studies showing cortical regions or networks related to cardiac activity-related measures, we showed ascending cardiac afferent signal-induced phase synchronization between cortical regions in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation